Obtaining a pancreatic cancer cell line stably expressing doxycycline-dependent endonuclease Cas9 - A.K. Nurgalieva; V.S. Skripova; L.F. Minigulova; R.G. Kiyamova (Учёные записки Казанского университета: Серия Естественные науки)
Pancreatic cancer is one of the most painful and aggressive types of cancer with high lethality rate. Early diagnosis of the disease is limited and antitumor therapy has low efficacy, because pancreatic cancer shows multiple drug resistance. It is still unclear how pancreatic tumor cells become resistant to chemotherapy and understanding of the resistance mechanisms and identification of their regulating genes is necessary to develop a new and more efficient pancreatic cancer therapy. One of the methods to identify such genes is CRISPR/Cas9 technology (clustered regularly interspaced short palindromic repeats) where Cas9 endonuclease is used to make double-strand DNA breaks in target genes. The aim of this work is modification of the pancreatic cancer cell line MIA PaCa-2 to express a doxycycline-inducible Cas9 endonuclease gene. Several plasmid vectors have been used to create a lentivirus containing the Cas9 endonuclease gene. The virus has been used for transduction of tumor cells to get doxycycline-inducible Cas9 expressing clones. Cas9 endonuclease expression has been detected by the western blot analysis with antibodies to FLAG epitope. Two tumor clones of the MIA Pa-Ca2/Cas9 cell line expressing Cas9 endonuclease have been generated. These cells can be used further to search genes related to regulation of the susceptibility to antitumor drugs.